Penerapan Model Discovery Learning Untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar Peserta Didik Kelas XI MIA1 di SMA Negeri 6 Konawe Selatan Pada Materi Pokok Optika Geometri dan Alat Optik - Tokase, Asmira; Anas, Muhammad; Sukariasih, Luh (Universitas Halu Oleo, 2021)
This study aims to: describe of increasing the science process skills and cognitive learning outcomes of students in class XI MIA1 SMA Negeri 6 Konawe Selatan on the subject matter of geometry optics and optical instrument by applying the discovery learning model. The subjects of this study were students of class XI MIA1 SMAN 6 Konawe Selatan in the even semester of the 2018/2019 school year, which amounted to 32 students. Data collection techniques were carried out with essay tests for cognitive learning outcomes and observation sheets for science process skills and the implementation of learning steps. Data analysis techniques using descriptive statistics. Based on the results of data the analysis and the discussion condudes: 1) Science process skills of students in class XI MIA1 SMAN 6 Konawe Selatan on the subject matter of geometry optics and optical instrument taught using discovery learning models have increased from the first cycle of the average score of science process skills all groups of students are in the sufficient category, whereas in cycle II all groups of students are in the good category. 2) The learning outcomes of students in class XI MIA1 SMAN 6 Konawe Selatan on the subject matter of geometry optics and optical instrument taught using discovery learning models have increased from cycle I the average value of learning outcomes by 73,13 whereas in cycle II the average value is 78,31.